Simultaneously Sizing and Quantitating Zeptomole‐Level DNA at High Throughput in Free Solution. Issue 43 (12th September 2014) - Zhu, Zaifang; Chen, Huang; Chen, Apeng; Lu, Joann J.; Liu, Shaorong; Zhao, Meiping
Abstract: Invited for the cover of this issue are the groups of Shaorong Liu at the University of Oklahoma and Meiping Zhao at Peking University. The top part of the image depicts a new but simple way to resolve DNA, which can be separated using only a piece of open narrow capillary; the bottom part depicts the high‐throughput and high‐resolution separation results. Read the full text of the article at 10.1002/chem.201403861 . Abstract : " The biggest challenges include injecting a short segment of DNA sample into an extremely narrow capillary and detecting a few molecules of DNA in such a capillary. " Read more about the story behind the cover in the Cover Profile and about the research itself on page 13945 ff. (DOI: 10.1002/chem.201403861 ).